Drug delivery across length scales. (16th March 2019) - Delcassian, Derfogail; Patel, Asha K.; Cortinas, Abel B.; Langer, Robert
Abstract: Over the last century, there has been a dramatic change in the nature of therapeutic, biologically active molecules available to treat disease. Therapies have evolved from extracted natural products towards rationally designed biomolecules, including small molecules, engineered proteins and nucleic acids. The use of potent drugs which target specific organs, cells or biochemical pathways, necessitates new tools which can enable controlled delivery and dosing of these therapeutics to their biological targets. Here, we review the miniaturisation of drug delivery systems from the macro to nano-scale, focussing on controlled dosing and controlled targeting as two key parameters in drug delivery device design. We describe how the miniaturisation of these devices enables the move from repeated, systemic dosing, to on-demand, targeted delivery of therapeutic drugs and highlight areas of focus for the future.